Dermal Papilla Cell-Derived Extracellular Vesicles Increase Hair Inductive Gene Expression in Adipose Stem Cells via β-Catenin Activation - Taheruzzaman Kazi; Abir Nagata; Takatoshi Nakagawa; Takashi Matsuzaki; Shigeki Inui (Cells, 2022)
Recently, extracellular vesicle (EV)-mediated cell differentiation has gained attention in developmental biology due to genetic exchange between donor cells and recipient cells via transfer of mRNA and miRNA. EVs, also known as exosomes, play a role in maintaining paracrine cell communication and can induce cell proliferation and differentiation. However, it remains unclear whether adipose-derived stem cells (ASCs) can adopt dermal papilla (DP)-like properties with dermal papilla cell-derived extracellular vesicles (DPC-EVs). To understand the effect of DPC-EVs on cell differentiation, DPC-EVs were characterized and incubated with ASCs, of monolayer and spheroid cell cultures, in combination with the CAO1/2FP medium specialized for dermal papilla cells (DPCs). DPC-like properties in ASCs were initially evaluated by comparing several genes and proteins with those of DPCs via real-time PCR analysis and immunostaining, respectively. We also evaluated the presence of hair growth-related microRNAs (miRNAs), specifically mir-214-5P, mir-218-5p, and mir-195-5P. Here, we found that miRNA expression patterns varied in DPC-EVs from passage 4 (P4) or P5. In addition, DPC-EVs in combination with CAP1/2FP accelerated ASC proliferation at low concentrations and propagated hair inductive gene expression for versican (vcan), alpha-smooth muscle actin (α-sma), osteopontin (opn), and N-Cam (ncam). Comparison between the expression of hair inductive genes (vcan, α-sma, ctnb, and others), the protein VCAN, α-SMA and β-Catenin (CTNB), and hair inductive miRNAs (mir-214-5P, mir-218-5p, and mir-195-5p) of DPC-EVs revealed similarities between P4 DPC-EVs-treated ASCs and DPCs. We concluded that early passage DPC-EVs, in combination with CAP1/2FP, enabled ASCs to transdifferentiate into DPC-like cells.